Longitudinal quantitative assessment of coronary plaque progression related to body mass index using serial coronary computed tomography angiography. (18th January 2019) - Won, Ki-Bum; Lee, Sang-Eun; Lee, Byoung Kwon; Park, Hyung-Bok; Heo, Ran; Rizvi, Asim; Hadamitzky, Martin; Kim, Yong-Jin; Sung, Ji Min; Conte, Edoardo; Andreini, Daniele; Pontone, Gianluca; et al.
Abstract: Aims: This study explored the coronary plaque volume change (PVC) according to the change of percent body mass index (BMI) and categorical BMI group using serial coronary computed tomography angiography (CCTA). Methods and results: A total of 1568 subjects who underwent serial CCTA with available BMI at baseline (CCTA1) and follow-up (CCTA2) were included. Median inter-scan period was 3.3 (interquartile range: 2.6–4.6) years. Quantitative assessment of coronary plaque was performed at both scans. All participants were categorized into three BMI (kg/m 2 ) groups: normal: <25.0; overweight: 25.0–29.9; and obesity: ≥30.0. During follow-up, there were no significant differences in annualized PVC according to the 5% change of BMI in all BMI groups. Among 1424 (90.8%) subjects in the same BMI group at CCTA1 and CCTA2, a significant difference in annualized (PVC) was observed among the three groups. In 144 (9.2%) subjects with the change in their BMI group at CCTA2 compared their results at CCTA1, annualized PVC was not different compared with subjects in the same BMI group during follow-up. The percent change of BMI was not significantly related to the annualized PVC after adjusting confounding factors. Male gender [odds ratio (OR): 1.38; 95% confidence interval (CI): 1.05–1.81; P = 0.022], baseline plaque volume (OR: 1.07; 95% CI: 1.05–1.09; P < 0.001), and baseline overweight or obesity (OR: 1.35; 95% CI: 1.04–1.77; P = 0.027) were independently associated with coronary plaque progression. Conclusion: Over the near term, longitudinal small changes in BMI were not associated with changes in coronary plaque volume although baseline BMI was. Clinical trial registration: ClinicalTrials.gov NCT02803411.